2016
DOI: 10.1111/codi.13254
|View full text |Cite
|
Sign up to set email alerts
|

Review of the quality of total mesorectal excision does not improve the prediction of outcome

Abstract: Any difference in grading of the TME specimen between local histopathologists and the review panel had no significant impact on the prediction of oncological outcome for this patient cohort. Grading of the quality of TME as reported by local histopathologists can therefore be used for outcome analysis. Quality control of TME grading is not warranted provided the histopathologist is adequately trained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…First, there was no central pathology review. The PROCARE study compared the quality of TME specimens as assessed by a central review panel and local pathologists for more than 250 patients with rectal cancer and found no major discrepancies, whereas the prediction of clinical outcomes was comparable. Hence, under the prerequisite of adequate pathologist training, a central review may not have led to a significant correction of individual pathology reports .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there was no central pathology review. The PROCARE study compared the quality of TME specimens as assessed by a central review panel and local pathologists for more than 250 patients with rectal cancer and found no major discrepancies, whereas the prediction of clinical outcomes was comparable. Hence, under the prerequisite of adequate pathologist training, a central review may not have led to a significant correction of individual pathology reports .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, under the prerequisite of adequate pathologist training, a central review may not have led to a significant correction of individual pathology reports. 28,33 Second, baseline MRI results…”
Section: Limitationsmentioning
confidence: 99%
“…The specific biological mechanism determining the association between NCM excision and CSS, but not LR or other cancer outcomes, is not easily explained, but reflects the variable and sometimes conflicting associations between mesorectal grading and cancer outcomes in the literature. In particular, there is conflicting evidence on the relationship between mesorectal grading and OS , OR rate and DR rate , and at least two series have indicated no significant association between mesorectal grading and cancer outcomes . Such wide discrepancy is likely to originate in the heterogeneity of study designs, variable sample sizes and reported lengths of follow‐up, which prompted our interest in conducting the present analysis.…”
Section: Discussionmentioning
confidence: 98%
“…TME performance and TME grading has been demonstrated to be standardizable and easily taught. [18][19][20] Concerted efforts to further standardize TME documentation and grading across other hospitals and specialties will likely result in improvement in these quality measures. 17,21,22 A single-institution study by Garcia-Granero, et al evaluated formal implementation of a macroscopic TME evaluation protocol and found that rates of TME assessment improved from 55% to 99% over a 10-year span.…”
Section: Discussionmentioning
confidence: 99%